The COVID-19 Vaccines: A Description of Adverse Events or Reactions Reported in Kansas - Mills, Kale; Tri, Anna; Nilsen, Kari (Kansas Journal of Medicine, 2022)
Introduction. Coronavirus disease 2019 (COVID-19) is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and has spread rapidly throughout the world since its discovery in 2019. Three vaccines (Pfizer-BioNTech, Moderna/NIAID/BARDA, and Johnson & Johnson’s Janssen) have been developed for use in the U.S. to aid in the fight against this virus, but have been scrutinized intensely for their efficacy and safety. It is important to understand and interpret the adverse events or reactions (AERs) associated with these vaccines in an objective and analytical manner. The goal of this descriptive study was to provide a resource outlining AERs associated with the three available vaccines in Kansas.Methods. Reports were obtained from the Vaccine Adverse Event Reporting System (VAERS), representing AERs observed in Kansas from December 11th, 2020, to May 13th, 2021. All data were screened and coded, and descriptive statistics were used to describe AERs based on vaccine manufacturer, age, gender, and reported deaths.Results. Only 0.068% of COVID-19 vaccines doses given were associated with an AER. The most common AERs were fatigue/tiredness, tingling/itching, fever, hives, and muscle/joint paint. Only 0.002% of reports to VAERS were associated with a death. The majority of reports were by females (78.8%) and those aged 30 to 39 (20.6%).Conclusions. No reported AERs were unexpected compared to national data, and no VAERs report provided a causal relationship between vaccine administration and death. Vaccines are, and will continue to be, essential tools to fight COVID-19. Providing a resource of potential AERs could aid in individual decisions to receive a vaccine and may help in the control of COVID-19.